Chlorhexidine Gluconate Dressings Reduce Bacterial Colonization Rates in Epidural and Peripheral Regional Catheters. (23rd March 2015) - Kerwat, Klaus; Eberhart, Leopold; Kerwat, Martina; Hörth, Dominik; Wulf, Hinnerk; Steinfeldt, Thorsten; Wiesmann, Thomas
Abstract : Introduction . Bacterial colonization of catheter tips is common in regional anesthesia and is a suspected risk factor for infectious complications. This is the first study evaluating the effect of CHG-impregnated dressings on bacterial colonization of regional anesthesia catheters in a routine clinical setting. Methods . In this prospective study, regional anesthesia catheter infection rates were examined in two groups of patients with epidural and peripheral regional catheters. In the first group, regional anesthesia was dressed with a conventional draping. The second group of patients underwent catheter dressing using a CHG-impregnated draping. Removed catheters and the insertion sites were both screened for bacterial colonization. Results . A total of 337 catheters from 308 patients were analysed. There was no significant reduction of local infections in either epidural or peripheral regional anesthesia catheters in both CHG and conventional groups. In the conventional group, 21% of the catheter tips and 41% of the insertion sites showed positive culture results. In the CHG-group, however, only 3% of the catheter tips and 8% of the insertion sites were colonised. Conclusion . CHG dressings significantly reduce bacterial colonization of the tip and the insertion site of epidural and peripheral regional catheters. However, no reductions in rates of local infections were seen.